FAKTOR-FAKTOR YANG MEMPENGARUHI FIRM PERFORMANCE PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Nathania Debora T Sofia Prima Dewi (Jurnal Paradigma Akuntansi, 2020)
The purpose of this research is to obtain empirical evidence about the effects of intellectual capital, leverage, firm size, and liquidity on firm performanceat manufacturing firms listed on Indonesian Stock Exchange during the period of 2015-2017. The data used in this research was secondary data in the form of financial information from the financial statements and annual reports. There were 64 samples of manufacturing companies that have been previously selected using purposive sampling method with total of 192data for three years. This research data was processed using EViews 10. Results shows that human capital efficiency, capital employed effiency and leverage has a significant influence on firm performance, while structural capital efficiency, firm size, and liquidity has no significant influence on firm performance.